Penyelesaian Utang Impor, Ju’alah Dan Sertifikat Bank Indonesia Syariah (SBIS) Perspektif Fatwa DSN-MUI - Khozainul Ulum (JES (Jurnal Ekonomi Syariah), 2018)
Sharia financial Institution is one of the economic supporters of Indonesia. It is evidenced by the number of Islamic financial institutions that have sprung up this year, both sharia bank and non-bank sharia financial institution. It accommodates the aspiration and need of the society. The public is given the widest opportunity to establish a bank based on sharia principles, including convert from commercial banks whose business activities are based on conventional patterns into sharia patterns. The more sharia financial institutions that emerge, the more products offered by Islamic financial institutions to customers with the level of risk that can be overcome. The writing aims to answer the formulation of problem of settlement of import debts, contract of ju’a>lah and Sharia Certificate of Bank Indonesia (SBIS) in perspective of DSN-MUI fatwa. The result of research shows that in the DSN-MUI fatwa, it is explained that the settlement of imported debt or we know as letter of credit (L/C) may use the kafa>lah contract by taking a fee. It is also explained that one of the forms of kafa>lah contract is kafa>lah bi al-ma>l which is the application of kafa>lah contract which guarantees the payment of goods or debt repayment. This guarantee may be provided by the sharia bank to its customers in return for a fee. For the settlement of import debt there are several contracts that can be used, namely the contract of h}iwa>lah bi al-ujrah, waka>lah bi al-ujrah, and kafa>lah bi al-ujrah The Sharia Certificate of Bank Indonesia which used to be wadi>’ah with Wadi>’ah Certificate of Bank Indonesia which is now changed with Sharia Certificate of Bank Indonesia uses ju’a>lah contract. In this contract, Bank Indonesia pays the repayment upon maturity of SBIS with the relevant sharia banking record having performed and achieving the objectives expected by Bank Indonesia. If the sharia banking concerned is not able to achieve the desired objectives or stipulated by Bank Indonesia in terms of monetary control based on sharia principles, the relevant sharia banking will not receive any compensation from Bank Indonesia. Keywords: Import Debt Settlement, Ju’a>lah, Sharia Certificate, Bank Indonesia, DSN-MUI Fatwa